A follow-up study of the first graduates of the Davao two-two plan - Cauilan, Eugenio B. 1905- ([Quezon City s.n.], 1960)
The purpose of this study is to secure data and information on the activities in the first year after graduation of the 193 students of the Davao City High School who were the first in this school to complete their secondary course under the Davao 2-2 plan. Attention will be directed to the academic work of those who continued their studies in college and to the status of those who stayed at home, put up their own business, or worked in shops, in offices, or in farms, with the aim of presenting records of performance.
Bibliography: l. 63-64.
Thesis (M.Ed.)--University of the Philippines, 1960
Typescript
Vita
Keywords: Education -- Davao (Province).